Dysaethria moza - Beljaev, Еvgeniy A.; Titova, Olga L. (Zenodo, 2023)
Dysaethria moza (Butler) (Fig. 3) Dysaethria moza : iNaturalist (2022a): GBIF occurrence 2465091989 (Sokol). Material examined. 10 ♂, 4 ♀, Sokhonda mount., 20, 21, 23, 26.VII.2019; 1 ♀, Razdolnoe, 26.VII.2019; 1 ♂, 3 ♀, S Kholmsk: 21.VII, 03, 05, 11.IX.2021. Distribution. Russia (S RFE: S * Sakhalin, S Kurils—Kunashir), Japan (from Hokkaido on the north up to Tsushima on the west and Amami Oshima on the south), south of North Korea, South Korea, N China (Shaanxi — BOLD Sample ID: BC ZSM Lep 29750, as “ Epiplema AH 01Ch”; GBIF occurrence 885130484). Remarks. In the GBIF, Andrei Humala (Forest Research Institute, Karelian Centre of Russian Academy of Sciences, Petrozavodsk, Russia) posted a photo of D. moza , taken 13.VII.2009 at Sokol village (Dolinskii distr., 47.2542º N, 142.8068º E) near the Okhotian coast of Sakhalin (iNaturalist 2022a). This locality is placed much to the northeast from our collecting places that indicates a wide distribution of this species in the southern part of the island. The finding of D. moza in Sakhalin significantly expand its distribution range to the north. It should be clarified that the literature reports of D. moza from the Kurils (Kunashir) are correct while the indication for Primorskii Krai is wrong due to a misprint in the first publication from the cited below (Tshistjakov 2005: 397; Sinev 2008: 190; Tshistjakov & Beljaev 2016: 518; Sinev 2019: 234; Sinev 2021; Zolotuhin & Nedoshivina 2021: 348, map). The host plants of D. moza in Japan are Viburnum dilatatum and V. erosum (Adoxaceae) (Sugi 1987). On Sokhonda mountain, the collected and observed moths were strictly associated with the V. furcatum thickets in the mountain spruce-fir forest. Obviously, this plant can be considered as a new host for this species. In Sakhalin D. moza likely develops in one generation, although the moths fly from mid-July to September. Published as part of Beljaev, Еvgeniy A. & Titova, Olga L., 2023, New data on geometroid moths (Lepidoptera: Geometroidea: Uraniidae and ...